Studi Literatur Dampak Perceraian Orang Tua terhadap Hubungan Sosial dan Sikap Egois Anak di SMK Swasta Mandiri - Harahap, Ade Chita Putri; Yasri, Ahmad; Mahyani, Alya; Syahputri, Eka; Aufa, Najia Barouatul; Siregar, Nova Susanti Br; Medy, Putri Aulia; Hidayati, Syari (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to investigate the impact of parental divorce on children's social relationships and selfish attitudes. Parental divorce is a complex event that can have long-term consequences for children's development. This study uses a qualitative approach in collecting data from children who have experienced their parents' divorce. The results of this study are expected to provide a better understanding of the social and psychological impact of parental divorce on children.